Investigating the use of fillers by kurdish efl university students in relation to speaking fluency - Abdullah, Dilbreen; Mohammed, Fakhir (Humanities Journal of University of Zakho, 2023)
The current study investigates the use of fillers produced by a sample of 80 Kurdish EFL university students (males and females), freshers and seniors, in relation to speaking fluency. The general methodological procedures of discourse analysis (hence, DA) by Potter and Wetherell (1987), Fairclough (1995) and Van Dijk (1997) have been followed to analyze the data extracted from the selected sample (i.e., spoken corpus). For finding the types of fillers, it was helpful to use Rose’s (1998) classification of fillers into unlexicalized fillers (UFs) and lexicalized fillers (LFs). Further, by using a speaking fluency rubric, the statistical correlation between fillers and speaking fluency was measured. The results showed that the lexicalized fillers (LFs) were used by the Kurdish EFL university students three times more than the unlexicalized fillers (UFs). Also, it was found that the most frequently used examples of UFs were Uh and Um, and the highest percentages of LFs were recorded for and, so, yeah and yes. With regard to speaking fluency levels, it was concluded that fillers are considered to be markers of mid or low levels of fluency. In other words, although fillers were also used in higher levels of fluency, however, the higher the level of fluency is, the lesser the use of fillers is.